Duhkha Dalam Chandogya Upanisad Dan Cara Mengatasinya - Joniarta, Made (Institut Hindu Dharma Negeri Denpasar, 2018)
The main purpose of this work is to conduct an investigation deep into the truth that reaches the step when someone becomes wise and mature to decide from all karma. The ChÄndogya Upaniá¹£ad text has been chosen to be studied in this study because this literature clearly explains the duá¸¥kha conception. The concept of duá¸¥kha in the ChÄndogya Upaniá¹£ad is a state of the soul that is materially bound to the physical body. When the soul is bound to the senses materially, it causes billions of desires to come out. All boundaries of these desires will throw the soul into the depths of grief (duá¸¥kha). The way to let go of the duá¸¥kha based on the ChÄndogya Upaniá¹£ad by understanding the atman which covers the universe, will experience unlimited happiness. Truly unlimited God is He transcends all that is. Thus Chandogya Upanisad encourages everyone to know and appreciate the true nature of the self, to be released from Dukha.